Attributable mortality due to fluoroquinolone and extended-spectrum cephalosporin resistance in hospital-onset Escherichia coli and Klebsiella spp bacteremia: A matched cohort study in 129 Veterans Health Administration medical centers. (August 2019) - Suzuki, Hiroyuki; Perencevich, Eli N.; Livorsi, Daniel J.; Alexander, Bruce; Beck, Brice F.; Richardson, Kelly K.; Goto, Michihiko
Abstract: In this cohort of Escherichia coli and Klebsiella spp hospital-onset bacteremia, isolated fluoroquinolone resistance had a larger relative impact on mortality than other phenotypic resistance patterns. This finding may support stewardship efforts targeting unnecessary fluoroquinolone use and increased attention from infection prevention and control departments.